Development of E-Modules of Integrated Temperature and Heat with STEM-Contextual Approach Of Papua - Anderias Henukh; Merta Simbolon; Ivylentine D Pallitin; Atia S Handayani (Asian Journal of Science Education, 2023)
This study intended to describe the results of the development of an e-module of integrated temperature and heat by using the STEM-contextual approach of Papua. This study was conducted at SMAS YPK. The subjects of this research were class X students of SMAS YPK Merauke who were used to test the product being developed. The research method used is Research and Development (RD) with the ADDIE development model. The instruments used in the study were validation sheets, teacher and student response questionnaires, and essay tests. The results of this study are products in the form of STEM-based e-modules. Expert validation results were conducted and show the result 90.6% for material, 91.66% for media, and 85.5% for linguists' parts respectively. Besides, the results of the student response questionnaire were 86.25%, and the teacher's response questionnaire was 97.91%. Therefore, it can be concluded that the development of an e-module of integrated temperature and heat with a STEM-contextual approach of Papua is very appropriate to be used in the physics learning process.